ANALYSIS OF THE INFLUENCE OF LOCATION, PRICE AND QUALITY OF SERVICE ON CONSUMER PURCHASE DECISIONS (Jurnal Ipteks Terapan, 2022)
This study aims to determine the effect of examination area, cost, and nature of the administration on the purchase choice of buyers at PT. Coronavirus Parade during the pandemic. The strategy used in this study is a quantitative methodology. Using the SPSS program to collect test information and test measurable investigations. H Result area of ​​this research variable Positive massive impact on critical purchase choices 0.008